E-learning, quality management, and higher education in the UAE: evolution and current landscape - Shraih, Hadia J. A.; Santos-Roldán, Luna; Maldonado, Miguel A.; Moyano, Manuel (Frontiers in Education, 2026)
IntroductionThis systematic review provides an overview of e-learning quality management in higher education institutions in the United Arab Emirates (UAE).MethodsA systematic bibliographic search of relevant academic databases was conducted, identifying 11 articles published between January 2019 and July 2024. The literature review integrates information on the following areas: institutional readiness and implementation, student readiness, satisfaction, and intention; factors influencing the adoption and quality of e-learning; management and assessment; the impact of COVID-19 on e-learning and professional development; and faculty perspectives. Additionally, a general summary of the methodological quality of the analyzed studies is provided.ResultsThe major issues discussed include the increased use of e-learning solutions due to governmental support, the necessity of culture-sensitive strategies, problems concerning academic and credit recognition, and possibilities for individualized learning and international cooperation. The review emphasizes the integration of the technological, pedagogical, and organizational aspects of the quality management approach. Solutions are proposed to enhance staff training and development processes, student services, and quality assurance systems in education that utilize information technologies. The study also outlines areas for future research, including a longitudinal study of all quality management practices and innovations in assessment methods for online learning.DiscussionThe findings of this research are beneficial for the UAE and enhance the understanding of e-learning quality management in the context of higher education in the region. It also informs policymakers and practitioners about various issues they may face.